1999
DOI: 10.1007/s003300050914
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary MR: Kidneys and adrenal glands

Abstract: Due to its high tissue contrast and multiplanar imaging capabilities, MRI provides a detailed display of renal and adrenal anatomy. Recent technical developments overcoming the problem of respiration induced motion artifacts and the use of paramagnetic contrast agents have further improved the performance of MRI which has now evolved as an alternative or complementary imaging modality to ultrasound, excretory urography and computed tomography. Dynamic contrast-enhanced studies will usually allow to detect even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Animal and patient studies have shown that the sole injection of gadolinium without a diuretic cannot safely provide a sufficient urographic effect [16,17]. The normal kidney function is able to concentrate the excreted amount of gadolinium inside the tubular system by a factor of 50±100 [18]. The particular value of low-dose furosemi-23 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and patient studies have shown that the sole injection of gadolinium without a diuretic cannot safely provide a sufficient urographic effect [16,17]. The normal kidney function is able to concentrate the excreted amount of gadolinium inside the tubular system by a factor of 50±100 [18]. The particular value of low-dose furosemi-23 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sensitivity 2 and specificity, 3 as well as increases of sensitivity and specificity from precontrast MRI to the combined precontrast and postcontrast MRI, were determined. No threshold for statistical significance was prospectively defined for the sensitivity and specificity datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The use of gadopentetate dimeglumine (0.5 M Gd-DTPA, Magnevist®, Bayer Schering Pharma) in combination with fat-saturation (FS) techniques has been shown to be superior to unenhanced MR imaging for detection and characterization of renal [2]. Furthermore, 0.5 M gadopentate dimeglumine may also provide the detection of functional kidney derangement [3,4] and allow for selective direct imaging of the entire urinary tract [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hormonally inactive adrenal adenomas are seen in ≈ 1% of the adult population. Moreover, those associated with thrombus in the IVC are even more rare [2].…”
Section: Discussionmentioning
confidence: 99%